Cyberattacks and data breaches in Indonesia by Bjorka: hacker or data collector? - Tole Sutikno; Deris Stiawan (Bulletin of Electrical Engineering and Informatics, 2022)
Recently, the public has been shocked by the mysterious figure of Hacker Bjorka. Bjorka hacked Indonesian officials. Bjorka leaks Indonesia's General Election Commission (KPU) data. This raises a significant red flag concerning Bjorka's ability to "disrupt" circumstances that are harmful to a large number of individuals, including his alleged action of leaking the personal data of influential state officials. Expert Putra Aji Adhari says Bjorka isn't a hacker. Aji Putra stated that Bjorka is a team. He, who has been invited to communicate with NASA, is sure Bjorka is still in Indonesia. Putra told Bjorka's hacking steps. Ardi Sutedja declared Bjorka isn't a person, his pattern mirrored a hacking group's. Sutedja knew Bjorka was Indonesian. Domestic targets, attacks, and mastery are evidences. On the other hand, Wiryana, as a hacker's handler, said that Bjorka is not a real hacker but rather a data collector. Ismail Fahmi says that a hacker like Bjorka uses a VPN to get to a server without leaving any traces. Bjorka might have come from Indonesia. One sign is that Bjorka's use of English is similar to how most Indonesians talk.